Biogas Production From Seaweed Padina sp - Herdiansyah Putra; R. Marwita Sari Putri; Aidil Fadli Ilhamdy (Marinade, 2019)
Seaweed have carbohydrates and water content is high as well as low lignin in comparison with terrestrial plants making it easier didegradasi. Therefore, making the seaweed as feedstock in the manufacture of biogas is one solution to improve the utilization of seaweed in Indonesia. The goal of the research is to find out the potential of seaweed type Padina sp with continuous systems in the manufacture of biogas. Seaweed padina sp has a k arakteristik: protein 4.54, moisture content, ash levels 45.16 12.52 and the ratio c/n 20.81 thus Padina sp potential raw material for the manufacture of biogas. The addition of seaweed padina sp when the biogas production process of 657.84 mg/L COD values before the biogas production process on the comparison of 1:1 of (786,195) and 1:2 (782,184) and the value of COD on after amounting to 1:1 (581,624) and 1:2 (569.59) that result in the concentration of methane (CH4) comparison of 1:1 (107.20 ppm) and 1:2 (123.30 ppm). Carbon dioxide (CO2) concentration of 1:1 (512.79 ppm) and 1:2 (527.39 ppm), respectively.